Three year performance of international provenance trials of Acacia auriculiformis - Awang, Kamis; Venkateswarlu, Perugupalli; Abd.Shukor, Nor Aini; Adjers, Goran; Bhumibhamon, Suree; Kietvuttinon, Bopit; Pan, Fuh-Juinn; Pitpreecha, Kiatkong; Simsiri, Apisit (1994)
The performance of 25 provenances in international trials on seven sites in four countries was assessed for survival and growth at 3 years. Of these provenances, seven were from Queensland, 12 from Northern Territory, Australia, and six from Papua New Guinea. Significant growth differences were found: (a) among provenances at four sites, (b) among the sites, and (c) between provenance regions. The interaction between sites and provenances as well as between sites and provenance regions was also significant. The poorest growth was recorded in Kanchanaburi, Thailand, while the best growth was in Banjarbaru, Indonesia. Stability analyses of the provenance x site interaction revealed eight provenances with high vigour and good tree form that were relatively stable across sites. These included Archer River, South Coen, Coen River and Wenlock River provenances from Queensland; Noogoo Swamp and Mann River provenances from Northern Territory; and North Bensbach and Old Tonda Village provenances from Papua New Guinea. © 1994.